Improvisation in the elementary music classroom - Rogers, Shelby Rose (Kansas State University, 2023)
For my project, I created a series of activities to facilitate fifth grade students’ learning that focused on improvisation, rhythm and solfege reading, and responding to music. The first of the activities of my lesson focused on responding to music. Given manipulatives, students show a variety of notes along with a chosen song. The second activity in my lesson involved reading and performing rhythms and solfege. I guided students as a class to determine what notes are being used, how to count the rhythm, and how to perform the specific rhythm or solfege. The last activity in the lesson focused on introductory improvisation. In small groups, I gave my students a series of rhythms to practice improvising. The groups needed to figure out the rhythm and perform that rhythm on any of the given notes. At the end of the lesson, most students were excited to make up their own music. More instruction would be needed when another improvisation activity is planned. During my time in Kansas State University’s Master of Music program, I realized that my students have created, moved, and responded to music more than before I began working towards my Master of Music degree. A major development in my teaching has been for me to integrate more improvisation and composition into my classroom. I realized earlier in the school year that I had not been allowing my students to express themselves as often as they could have by creating their own music. If I were to inspire my students to be lifelong learners and musicians, as well as taking away any hesitancy of improvising, I would need to incorporate more creating in my classroom. If my goal is to inspire my students in that way, they should be able to connect music to other areas of their lives. Since my time in the master’s program, I have become more comfortable with myself in the classroom. I am determined to show my students that music can follow you throughout your life and build connection with those around you.
Keywords: Elementary music; Music education; Improvisation